Stress Intensity Factors - T-Stresses - Weight Functions. Supplement Volume - Fett, Theo (Schriftenreihe des Instituts für Keramik im Maschinenbau - IKM, 2010)
Stresses in the vicinity of the crack tips are responsible for failure of crack-containing components. The singular stress contribution is characterised by the stress intensity factor K, the first regular stress term is represented by the so-called T-stress. Whereas in the main volume, IKM 50, predominantly one-dimensional cracks were considered in homogeneous materials, this supplement volume compiles new results on one-dimensional and two-dimensional cracks.